How to Adapt Anesthetic Human Resources to Health Emergencies Such as the COVID-19 Outbreak: Replacing a Pre-anesthetic Consultation With a Questionnaire in a University Obstetric Unit - Boussac, Emilie; Gery, Charlene; Desseauve, David (Frontiers in Medicine, 2022)
To deal with a reorganization of the Pre-Anesthetic Consultation during COVID-19 pandemic, a screening questionnaire was created and sent to anesthetic risk parturients at the Pre-Anesthetic Consultation. This innovative approach enabled the redistribution of medical anesthetic resources in units heavily affected by the pandemic.